Linking the past and the present: service users' perspectives of how adverse experiences relate to their admission to forensic mental health services. Issue 1 (30th December 2021) - Cartwright, Jessica; Lawrence, Daniel; Hartwright, Christopher
Abstract : Purpose: This study aimed to explore how forensic mental health service users make sense of their past adverse experiences. Secondly, it aimed to explore whether service users considered their adverse experiences to be related to their current stay in a forensic mental health setting. Design/methodology/approach: Interpretative phenomenological analysis was used to analyse interviews with eight service users in low and medium secure care. Six of the participants were male and two were female. Findings: Four super-ordinate themes emerged from the data: "Living amongst adversity"; "Managing adverse experiences"; "Making sense of going into secure care"; and "Coping with the past in the present". All participants referred to multiple adverse experiences throughout their lives and used harmful coping strategies to manage these. Individual differences in how they related their past experiences to their detention in secure care were evident. Practical implications: Author guidelines state that this section is optional. Implications for clinical practice are discussed at length in the discussion section. Originality/value: This study offers an insight into the way in which forensic mental health service users make sense of their past traumas in relation to their current admission to secure services. To the best of the authors' knowledge, no research has previously addressed this from the perspective of service users.